Hubungan Tipe Kepribadian dengan Sikap Remaja Pria Tentang Merokok di SMK 2 Yogyakarta - Nur Indah Febriliana, Purwanta, Dwi Harjanta (Berita Kedokteran Masyarakat (BKM), 2008)
Background: The age  for  the  initiation of smoking  tends  to  be younger every year. The  result of a study shows that  the  initiation of smoking  tends  to be  less  than 20  years of age. Whereas according  to another study  in  four of  Senior  high  schools  of Yogyakarta  randomly  chosen,  the  proportion  of  male  smokers  (trial  and  active smokers)    is equal,  i.e. 28.3%. There  are  factors which  cause  teenagers  to smoke,  one of which  is  personality factor. This  study  observes  the  relationship between  types  of  personality  (extrovert,  introvert  and  ambivert) and  attitude  about smoking  among male  teenagers.Objective: To  identify  the  relationship  between  types  of  personality  and  attitude  of male  teenagers  about smoking  at SMK  2 of Yogyakarta.Method: This was a  survey with  cross sectional  design. There were  as many  as 59  respondents consisted  of 30  respondents of grade  I and 29  respondents of grade  II chosen using proportionate stratified  random sampling technique.  Instruments  of  the  study were  questionnaires  and  data analysis  used  chi  square at  deviation=2.Result: There were  31  students of  ambivert  personality  (52.5 %).  The majority  of  respondents  had  positive attitude about  smoking,  i.e.  33  respondents  (55.9%). Students  of  introvert  personality  tended  to  have  positive attitude  as many  as 14.625  times higher  than  those  of extrovert  personality. The  result of  data analysis  showed that X2=9.323  and  p=0.009with N=59,  deviation=2. When  p<0.05 CI95%, HO was  denied. Therefore  since p=0.009  and p<0.05, HO was  denied. Accordingly  it could  be concluded  that  there was  relationship  between types  of personality  and attitude  of male  teenagers  about  smoking.Conclusion: There  was  relationship  between  types  of   personality  and  attitude  of male  teenagers  about smoking  at SMK  2 of Yogyakarta.Keywords:  extrovert,  introvert,  ambivert, attitude,  smoking,  teenagers